2010
DOI: 10.1152/jn.00985.2009
|View full text |Cite
|
Sign up to set email alerts
|

Central Gustatory Neurons Integrate Taste Quality Information From Four Appendages in the Moth Heliothis virescens

Abstract: Discrimination between edible and noxious food, crucial for animal survival, is based on separate gustatory receptors for phagostimulants and deterrents. In the moth Heliothis virescens, gustatory receptor neurons (GRNs) tuned to phagostimulants like sucrose and deterrents like quinine, respectively, have indicated a labeled line mechanism for mediating appetitive and aversive information to the CNS. In the present study, we have investigated the central gustatory neurons (CGNs) in this moth as an approach to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…The effect of pre-exposure to both sucrose and quinine on sucrose responses was highly similar, in spite of quinine being a feeding deterrent (i.e. an aversive signal) in phytophagous insects [26], [37][39], whereas sucrose is an appetitive stimulus. To our knowledge, this is the first time that a brief exposure to tastants is shown to increase behavioural responses to the same or even a different chemical stimulus after one whole day.…”
Section: Discussionmentioning
confidence: 92%
“…The effect of pre-exposure to both sucrose and quinine on sucrose responses was highly similar, in spite of quinine being a feeding deterrent (i.e. an aversive signal) in phytophagous insects [26], [37][39], whereas sucrose is an appetitive stimulus. To our knowledge, this is the first time that a brief exposure to tastants is shown to increase behavioural responses to the same or even a different chemical stimulus after one whole day.…”
Section: Discussionmentioning
confidence: 92%
“…All of our analyses involve calculating response firing rates within particular time periods, extending the large multi-species corpus of studies in which concentration- and palatability-related information has been found in firing rates (Ganchrow and Erickson, 1970; Di Lorenzo and Schwartzbaum, 1982; Yamamoto, 1984; Spector et al, 1988; Scott et al, 1991; Chalansonnet and Chaput, 1998; McCaughey and Scott, 1998; Nishijo et al, 1998; Boughter et al, 1999; Duchamp-Viret et al, 2000; Katz et al, 2001; Rogers and Newland, 2002; Wachowiak et al, 2002; Taha and Fields, 2005; Tindell et al, 2006; Grossman et al, 2008; Chandrashekar et al, 2010; Haddad et al, 2010; Kvello et al, 2010). Here, we analyze the presence and timing of both properties in cortical and amygdalar taste responses, bringing an identical battery of tests to bear on responses of each region.…”
Section: Methodsmentioning
confidence: 99%
“…Feeding in Drosophila larvae has been shown to make use of a CPG in the SEZ (Schoofs et al 2010(Schoofs et al , H€ uckesfeld et al 2015. In the SEZ of an adult moth, an interneuron was recorded that showed phasic activity to a tonic sugar stimulus (Kvello et al 2010), making it a good candidate for a component of a CPG. Since proboscis extension and pumping can be uncoupled, they might make use of two CPGs; it is thought that pumping can only be elicited by stimulation of the proboscis, whereas proboscis extension can be triggered by stimulating either the leg or proboscis (Dethier 1976, Vosshall and.…”
Section: Interneuronsmentioning
confidence: 99%